Thermal stability and dynamics of soft nanoparticle membranes: role of entropy, enthalpy and membrane compressibility. Issue 4 (2nd January 2020) - Das A, Nimmi; Begam, Nafisa; Chandran, Sivasurender; Swain, Aparna; Sprung, Michael; Basu, J. K.
Abstract : Tuning thermal stability soft nanoparticle membranes through entropic and enthalpic interactions with substrates. Abstract : Nanoparticle based ultra-thin membranes have been shown to have remarkable mechanical properties while also possessing novel electrical, optical or magnetic properties, which could be controlled by tailoring properties at the level of individual nanoparticles. Since in most cases the ultra-thin membranes are coupled to some substrates, the role of membrane–substrate interactions, apart from nanoparticle–nanoparticle interactions become very crucial in understanding their mechanical and thermal stability, as well as their plethora of applications. However, systematic studies in this direction have been conspicuously absent. Here we report thermal stability and the corresponding microscopic dynamics of polymer supported ultra-thin membranes comprising of self-assembled, ordered grains of polymer grafted nanoparticles having tunable mechanical properties. The initially ordered membranes show distinct pathways for temperature induced disordering depending on membrane flexibility as well as on interfacial entropic and enthalpic interactions with the underlying polymer thin film. We also observe contrasting temperature dependence of microscopic dynamics of these membranes depending on whether the graft polymer–substrate polymer interactions are predominantly entropic or enthalpic in nature. Our results suggest that apart from their varied applications, the soft nanoparticle–polymer hybrid membranes are a playground for rich physics involving subtle entropic and enthalpic effects along with the nanoparticles softness, which eventually determine their thermo-mechanical stability.